EFFECT OF SHARING FUNDS (DBH) FOR REGIONAL BUDGET INCOME (APBD) PRODUCING REGIONS (STUDIES IN INDONESIA UPSTREAM OIL AND GAS INDUSTRY) - Kasman Arifin; Dina Hidayat; Halimahtussakdiah (Dinasti Publisher, 2021)
Revenue-sharing is an oil-producing region allocation is used as the working area of mining. Along with fiscal decentralization and greater regional autonomy lately, the revenue sharing should be used in order to increase the prosperity of oil and gas producing regions through APBD revenue. This study aims to determine the effect of profit sharing funds in the upstream oil and gas industry in Indonesia on the regional budget. This research is associative explanative. Data collected through interviews, questionnaires, observation and literature study. Data were analyzed descriptively, tested assumptions, estimated through path coefficients and confirmatory factor analysis. After that the model is interpreted and modified. The results show that the effect of revenue sharing funds on the regional budget is significant. The greater the revenue sharing funds, the greater the APBD producing regions.